The Role of Registries in Neurotrauma Research: Translating Data Into Health Policy That Enhances Patient Care; Comment on "Neurotrauma Surveillance in National Registries of Low- and Middle-Income Countries: A Scoping Review and Comparative Analysis of Data Dictionaries" - Nqobile Thango; Ronnie E. Baticulon; Laura Lippa (Kerman University of Medical Sciences, 2023)
The paucity of robust neurotrauma data is felt most in regions that experience a higher burden of traumatic brain injury (TBI). The scoping review done by Barthélemy et al provides insight into the current state of national registries in low- and middle-income countries (LMICs) while also exploring the tools required to standardize data collection. In this commentary, we reflect on the barriers to data collection (ie, creation and maintenance of a TBI registry) and explore how registries can aid both scientific output and preventative public awareness campaigns that may pave the way to improved health policy and social change that avert mortality and morbidity from TBI.